A influência da responsabilidade social empresarial na satisfação e fidelidade do cliente : um estudo com compradores de automóveis - Carreira, Daniela Rodrigues (2010)
This study presents an investigation of the influence of Corporate Social Responsibility (CSR) in customer s satisfaction and loyalty through a study with car s buyers, besides that, it aims to contribute to conceptual models of satisfaction and loyalty analysis by applying the model of Johnson et al. (2001), adapted for the introduction of variables of CSR and conscious consumption, in a car dealership in Natal / RN. The methodology has a descriptive quantitative approach and for the analysis results were applied statistical methods of simple and multiple linear regression analysis, descriptive analysis and exploratory analysis. The field research provided 90 valid forms. The results show that CSR affects the image of the company studied and is also one of the elements of the compound of satisfaction and loyalty. This study concludes that CSR should be considered in the strategic and marketing actions of firms